Morphological and community changes of turf algae in competition with corals (2015)
ABSTRACT: The morphological plasticity and community responses of algae competing with corals have not been assessed. We evaluated eight morphological characters of four species of stoloniferous clonal filamentous turf algae (FTA), including Lophosiphonia cristata (Lc) and Polysiphonia scopulorum var. villum (Psv), and the composition and number of turf algae (TA) in competition for space with the coral Orbicella spp. under experimental and non-manipulated conditions. All FTA exhibited morphological responses, such as increasing the formation of new ramets (except for Psv when competing with O. faveolata). Opposite responses in the space between erect axes were found when Psv competed with O. faveolata and when Lc competed with O. annularis. The characters modified by each FTA species, and the number and composition of TA species growing next to coral tissue differed from that of the TA growing at ≥3 cm. The specific and community responses indicate that some species of TA can actively colonise coral tissue and that fundamental competitive interactions between the two types of organisms occur within the first millimetres of the coral−algal boundary. These findings suggest that the morphological plasticity, high number, and functional redundancy of stoloniferous TA species favour their colonisation of coral tissue and resistance against coral invasion.